The association of sun sensitivity, sun protective behaviors and depression in both genders: a study based on the U.S. population - Zhang, Jipeng; Mo, Hongfei; Zhong, Xinruncheng; Feng, Rui (Frontiers in Public Health, 2025)
ObjectiveThe purpose of this study was to analyze the association between sun sensitivity, common sun protective behaviors (stay in shade, wear long sleeves, use sunscreen) and depression, respectively, in both genders, after adjusted for each other as confounders.Materials and methodsData from the National Health and Nutrition Examination Survey 2017–2018 cycle were aggregated. Sun sensitivity and sun protective behaviors were assessed through the dermatology questionnaire. Depression was assessed through the 9-item Patient Health Questionnaire, with a score > 4 as the cutoff point. Gender specific logistic regressions were carried out to analyze the association between sun sensitivity, sun protective behaviors and depression.ResultsA sample of 2,605 participants (mean age 39.99 ± 11.57 years) was analyzed, including 1,227 (47.1%) males and 1,378 (52.9%) females. No association between sun sensitivity and depression was observed. In the sample, stay in shade (OR = 1.27, 95% CI: 1.03–1.57) was positively associated with depression, use sunscreen (OR = 0.69, 95% CI: 0.53–0.90) was negatively associated with depression. Gender specific regressions showed no associations between sun protective behaviors and depression in males; both wear long sleeves (OR = 0.65, 95% CI: 0.42–0.99) and use sunscreen (OR = 0.71, 95% CI: 0.52–0.97) were negatively associated with depression in females.ConclusionNo association between sun sensitivity and depression. Stay in shade was positively associated with depression, while use sunscreen was negatively associated. Gender differences were observed: no association between sun protective behaviors and depression in males; wear long sleeves and use sunscreen may be negatively associated with depression in females.